Fenologia e biologia floral de três espécies simpátricas de Psychotria L. (Rubiaceae) em floresta estacional em Santa Maria, RS, Brasil - Pelissaro, Taise Maria (2012)
Species of the genus Psychotria L. are common in the understory of tropical and subtropical forest formations. Most species are distylous with two floral morphs (thrum and pin) in the same population, however homostylous and monomorphic species are common. The objective of this work was to monitor the vegetative and reproductive phenology, as well as determine aspects of floral biology, with emphasis on floral morphometric and floral visitors of Psychotria leiocarpa Cham. & Schltdl., P. carthagenensis Jacq. e P. myriantha Muell. Arg. found in Seasonal Deciduous Forest fragment in Boca do Monte, Santa Maria, RS (53º54 W, 29º38 S). The phenological monitoring was performed every fortnight from August 2010 to August 2011. Were evaluated the vegetative phenophases (budding and leaf fall) and reproductive flowering (anthesis and bud) and fruiting (immature and mature fruit). Were observed during flowering period and duration of anthesis and floral visitors, and collected flowers for morphometric analysis and pollen viability. The three species have intraspecific synchrony in all phenophases. Leaf fall occurred throughout the year, but was more expressive P. leiocarpa in the months of autumn and winter, in other species restricted to a few leaves. The leaf emission was synchronic and occurred in spring, followed by the issue of buds. The bloom was like the annual intermediate for the three species and occurred between October and January. There was greater synchrony between P. leiocarpa and P. carthagenensis, P. myriantha has a slight delay in peak bloom. The fruiting is synchronic, and fruit maturation is gradual and long-term during the autumn and winter. The precipitation was not correlated with any of the phenophases. The highest correlations were obtained for immature fruit with ripe fruit temperature and with temperature and day length. In P. leiocarpa period of anthesis was from 5 to 17 hours. P. myriantha anthesis took several periods during the day, and lasts for 24 h. In P. carthagenensis anthesis occurred in two periods: between 5 to 18 hours and between 12 hours until the next morning. P. myriantha is homostílica. P. leiocarpa has the two floral morphs, reciprocal herkogamy and not isopletic. It has dimorphic traits auxiliary corolla length, size of the stigma lobes and the size of pollen grains, and higher in thrum flowers corolla diameter and number of pollen grains per anther, the higher pin flowers. P. carthagenensis has the two floral morphs, without reciprocal herkogamy and is not isopletic. Presented dimorphic traits auxiliary, length of stigma lobes and anther size, higher in thrum morph and diameter of the corolla in higher pin morpho. The floral visitors were insects, especially of the order Hymenoptera. Apis mellifera was the most frequent visitor in P. leiocarpa and P. myriantha. P. carthagenensis has native bees as the most frequent visitors